THE IMPACT OF AGE AND PHYSIOLOGICAL STAGE ON SOME BIOCHEMICAL PARAMETERS AND IMMUNE GLOBULIN IN LOCAL AND CROSSBREED HOLSTEIN DAIRY COWS - Fallah Abd-Almohssien Abdalla AL-Asadi; Waleed Y. K; Khalaf A. H. Al-Rishdy (European Journal of Agricultural and Rural Education, 2024)
This study was conducted in one of the animal fields in the Abi AlKhassib area to investigate the impact of age and physiological stage on some biochemical parameters in the serum of local and crossbreed Holstein dairy cows. A total of 32 cows, including 16 local cows and 16 crossbreed Holstein cows, aged between 3 and 6 years were used during the period between 1st December 2019 to 31th May 2020, the total period of the experiment was 6 months, divided into two physiological stages: 3 months before parturition (gestation) and 3 months after parturition (lactation). The results showed a significant (p <0.05) increase in the concentrations of most biochemical parameters (cholesterol, glucose, triglycerides, urea, total protein, IgA, IgG, IgM, ALP) in older cows compared to younger cows, except for the ALT and AST enzyme concentrations. Pregnant cows had significantly(p><0.05) higher levels of cholesterol, triglycerides and total protein compared to lactating cows, while lactating cows had significantly (p><0.05) higher levels of glucose, urea, enzymes (ALT, AST, ALP), and immunoglobulins (IgA, IgG, IgM). Additionally, the crossbred (H×L) cows had significantly (p><0.05) higher levels in cholesterol, glucose, triglycerides, urea total protein and ALP compared to the local breed cows. Whereas, the local breed cows recorded significantly (p><0.05) higher levels of ALT and AST enzymes and immunoglobulins (IgA, IgG, IgM) in the serum compared to the crossbred cows>